The Influence of Electronic Word of Mouth, Perceived Quality, and Brand Image on Fashion Purchase Decisions - Satria Sandy Qodlyzzaka; Titik Desi Harsoyo (Arthatama: Journal of Business Management and Accounting, 2025)
This study is driven by the rising competition in the fashion sector, prompting brands to recognize and comprehend the key elements that affect consumer buying behavior. Within the realm of digitalization, electronic word of mouth, perceived quality, and brand image are acknowledged as crucial factors that can influence consumers’ buying choices. This research aims to examine how E-WOM, perceived quality, and brand image affect the purchasing choices of Roughneck 1991 customers in Yogyakarta. A quantitative research approach was utilized, with primary data gathered by distributing questionnaires to customers of Roughneck 1991. The gathered data were then examined through multiple linear regression methods to evaluate the influence of each independent variable on buying choices. The findings suggest that both E-WOM and perceived quality have no significant impact on consumers' purchasing decisions. On the other hand, brand image shows a strong and positive impact and is recognized as the key factor influencing purchasing choices. These results indicate that shoppers often place greater importance on brand image compared to other factors when purchasing fashion items. As a result, strengthening and upholding a robust brand image is essential for fashion brands to sway consumer choices and stay competitive in the market successfully.